Assessing Multidimensional Poverty Based on the Sustainable Livelihood Framework: A Case Study of Hang Kia and Pa Co Communes, Mai Chau District, Hoa Binh Province - Lieu, Dang Huu; Thanh, Nguyen Thi Ha (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 4DO - 10.25073/2588-1094/vnuees.4191, 2017)
Vietnamese government is officially applying standards of multidimensional poverty as a basis for poverty assessment in the period of 2016 and 2010, overcoming limitations of income poverty’s assessing methods. However, according to the authors’ point of view, the selected indicators have not yet reflected the comprehensive aspects of life, while multidimensional poverty assessment (driven from OPHI) based on sustainable livelihood framework (of DFID) is considered as a better method. This research is conducted in Hang Kia and Pa Co, the mountainous communes of Mai Chau district, Hoa Binh province, by using the later methods. Total 13 indicators under 5 livelihood sources were selected. As the results, the rates of multidimensional poverty in these two communes were shown by the insufficiency in each indicator, by communes and by kinds of poverty households. This result can be used for better decision- making on poverty reduction. Keywords Multidimensional poverty, sustainable livelihood, Hang Kia, Pa Co References [1] Lasse Krantz (2001), An Introduction: The Sustainable Livelihood Approach to Poverty Reduction, Swedish International Development Cooperation Agency, Division for Policy and Socio-Economic Analysis. [2] OPHI (2014), “Global Multidimentional Poverty Index 2014”, Oxford University. [3] Đặng Nguyên Anh, “Nghèo đa chiều ở Việt Nam: một số vấn đề chính sách và thực tiễn”, Trang thông tin điện tử của Ban Kinh tế Trung ương, https://kinhtetrunguong.vn/, đăng ngày 14/06/2016, truy cập ngày 26/11/2016. [4] Ngô Trường Thi (2014), “Tiến tới tiếp cận đo lường nghèo đa chiều ở Việt Nam”, http:// http://www.molisa.gov.vn/, đăng ngày 05/04/2014, truy cập ngày 26/11/2016 [5] DFID (1999), “Sustainable Livelihoods Guidance Sheets”. [6] Sabina Alkire, James Foster (2009), “Counting and Multidimensional Poverty Measurement” OPHI Working paper. [7] Đặng Hữu Liệu (2016), “Mối quan hệ giữa nghèo đói và độ đa dạng các hoạt động sinh kế: nghiên cứu trường hợp tại xã Hang Kia, Pà Cò huyện Mai Châu, tỉnh Hòa Bình”, Tạp chí Khoa học Đại học Sư phạm Hà Nội, tr.150-158, 61(10). [8] Solomon Asfaw, Nancy McCarthy, Adriana Paolantonio, Romina Cavatassi, Mulubrhan Amare and Leslie Lipper (2015), Livelihood diversification and vulnerability to poverty in rural Malawi, ESA Working Paper No. 15-02, Food and Agriculture Organization of the United Nations, Rome.